PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN DISIPLIN KERJA TERHADAP KINERJA PERANGKAT DESA DI KECAMATAN MADUKARA KABUPATEN BANJARNEGARA - Aryoko, Yudhistira Pradhipta; Purnadi, Purnadi; Darmawan, Akhmad (Universitas Muhammadiyah Metro Lampung, 2020)
The purpose of the study is to determine the influence of variables of transformational leadership style and working discipline towards the performance of village devices. This research uses a case study method conducted against the village device in Madukara Sub-district, Banjarnegara district. Questionnaires were distributed to 173 village device people. The result of this research has a number of advices for village officials, especially in Madukara sub-district of Banjarnegara district, to further improve its performance so that the village governance system is well maintained. The data analysis technique used is test of multiple linear regression analysis. The results showed that variables of the transformational leadership style (X1) were significantly affected by the performance (Y) variables. Then the work discipline variable (X2) significantly affects the performance variable. Variables of the transformational leadership style and work discipline are simultaneously affecting the performance variables. The working discipline variable is the variable that most affects the performance of village devices in Madukara sub-district, Banjarnegara district.Keywords: Transformational Leadership, Work Discipline, Performance